Indigenous heritage and rock art : worldwide research in memory of Daniel Arsenault - Charette, Carole,; Mazel, Aron D.,; Nash, George,; Arsenault, Daniel, (Archaeopress Archaeology, 2021)
Professor Daniel Arsenault, a leading exponent of Canadian Shield rock art, sadly passed away in 2016. This book contains 14 thought-provoking chapters dealing with Daniel's first love - the archaeology of artistic endeavour. It provides the reader with new ideas about the interpretation and dating of rock art, ethnography, heritage and material culture.